Kinetic study of acetic acid (vinegar) production from start fruit juice in a bioreactor - Abdul Karim, Mohamed Ismail; Jamal, Parveen; Kamaruddin, Noor Izzaida (Journal of Pure and Applied Microbiology, 2014)
A two stage fermentation process for production of acetic acid using star fruit juice with Saccaromycescerevisiae and Acetomonasacetii was conducted in a 2 L stirred tank bioreactor. The effect of inoculum size ( 5%,10%,15%) and agitation speed ( 250 rpm, 300 rpm, 350 rpm) on ethanol and acetic acid production of the juice were evaluated. Kinetic parameters on specific growth rate, yield, doubling time (i.e. ?,Yp/s. td,) of the fermentation process were also recorded. The optimum condition obtained from this batch fermentation was at 250 rpm of agitation speed and 5% inoculums sizes with the maximum product yield (Yethanol/glucose) of 0.859 g/g and (Y Acetic acid/Ethanol) of 0.342 g/g. The maximum specific growth rate, ? was 0.097h-1 for Saccharomyces cerevisiae while 0.085h-1 for Acetobacteraceti using initial glucose concentration of 20%. Using Central Composite Design experiment, for optimization of acetic acid production, the R2 value of 0.8372 was achieved and the highest acetic acid production obtained was 2.76 %TA while highest ethanol obtained was 17.8% or equivalent to 140.64 g/L. The above findings can be further utilized in fermentation process to produce vinegar in large amount from our tropical star fruit, Averrhoacarambola juice.